Perceptions of Artificial Intelligence (AI) in the Construction Industry Among Undergraduate Construction Management Students: Case Study—A Study of Future Leaders - Jonghoon Kim; Soomin Park; Sarah Moukhliss; Kwonsik Song; Dan Koo (Buildings)
This study investigates the perceptions of artificial intelligence (AI) among undergraduate construction management students who are poised to become future leaders in the construction industry. As the industry increasingly adopts AI technologies to enhance project planning, design, site management, and safety, understanding students’ attitudes toward these innovations becomes crucial. This research employs a mixed-methods approach, combining quantitative survey data with qualitative data to capture the students’ insights on AI’s potential applications, benefits, and challenges within the construction sector. Findings indicate that while students recognize AI’s transformative potential to improve efficiency and safety in construction processes, they also express concerns regarding ethical implications, job displacement, and the necessity of new skills to effectively integrate AI into their future careers. Additionally, this study reveals a significant gap in students’ knowledge about AI technologies and their applications in the construction industry. These insights underscore the importance of incorporating AI-focused curricula in construction management programs to better prepare students for the evolving landscape of the industry. Ultimately, this research contributes to the understanding of how the next generation of construction professionals perceives AI and highlights the need for educational institutions to adapt their programs to equip students with the competencies required for a technology-driven future.